2012
DOI: 10.1093/cvr/cvs276
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of post-intervention arterial remodelling

Abstract: It has been appreciated over the past two decades that arterial remodelling, in addition to intimal hyperplasia, contributes significantly to the degree of restenosis that develops following revascularization procedures. Remodelling appears to be an adventitia-based process that is contributed to by multiple factors including cytokines and growth factors that regulate extracellular matrix or phenotypic transformation of vascular cells including myofibroblasts. In this review, we summarize the currently availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
98
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 70 publications
0
98
0
Order By: Relevance
“…This can be considered an exaggerated form of wound healing characterized by luminal (re)narrowing due to smooth muscle hyperplasia and rapid vascular remodelling of the instrumented vessel [1]. The formation of neointima is a complex and multifactorial process, but excessive VSMC (vascular smooth muscle cell) proliferation and migration, inflammation and the production of large amounts of ECM (extracellular matrix) are all involved [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be considered an exaggerated form of wound healing characterized by luminal (re)narrowing due to smooth muscle hyperplasia and rapid vascular remodelling of the instrumented vessel [1]. The formation of neointima is a complex and multifactorial process, but excessive VSMC (vascular smooth muscle cell) proliferation and migration, inflammation and the production of large amounts of ECM (extracellular matrix) are all involved [2].…”
Section: Introductionmentioning
confidence: 99%
“…In a rabbit model of balloon injury, there is early upAbbreviations: 2-ClHDA, 2-chlorohexadecanal; ApoE, apolipoprotein E; BrdU, bromodeoxyuridine; DAB, 3,3-diaminobenzidine; ECM, extracellular matrix; FCS, fetal calf serum; i.p., intraperitoneal; LCA, left carotid artery; LDL, low-density lipoprotein; MPO, myeloperoxidase; oxLDL, oxidized low-density lipoprotein; PAPC, 1-palmitoyl-2-arachidonoyl-sn-glycero-3-phosphocholine; PC, phosphatidylcholine; PE, phosphatidylethanolamine; PGPC, 1-palmitoyl-2-glutaroyl-sn-glycero-3-phosphocholine; POVPC, 1-palmitoyl-2-oxovaleroyl-sn-glycero-3-phosphocholine; PS, phosphatidylserine; RCA, right carotid arteries; SOPC, 1-stearoyl-2-oleoyl-sn-glycero-3-phosphocholine; VSMC, vascular smooth muscle cell; αSMA, α smooth muscle actin. 1 Correspondence: Simon Kennedy (e-mail simon.kennedy@glasgow.ac.uk).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that a majority of patients undergo re-stenosis after the primary angioplasty procedures within 6 months of the treatment [10]. A number of laboratories have been working to understand the mechanism for the same.…”
Section: Role Of Insulin and Igfs In Vascular Restenosismentioning
confidence: 99%
“…In another in-vitro study, it has been shown that TGF beta and Smad3 treated smooth muscle cells (in vitro model for vascular injury) lead to increased secretion of CTGF and IGFII from vascular smooth muscle cells which in-turn stimulated collagen III more than Collagen I from vascular fibroblasts thus leading to adaptive vessel remodelling [4,10].…”
Section: Role Of Insulin and Igfs In Vascular Restenosismentioning
confidence: 99%
See 1 more Smart Citation